Rola Rządowego Centrum Legislacji w procesie tworzenia rządowych projektów aktów prawnych: [The role of the Government Legislative Centre in the proces of creating governmental drafts of legal acts] (Studia Prawnicze / The Legal Studies, 2006)
Rządowe Centrum Legislacji, w skrócie zwane RCL, utworzone zostało 1 stycznia 2000 r. na podstawie znowelizowanej między innymi w tym celu ustawy z dnia 8 sierpnia 1996 r. o Radzie Ministrów (tekst jedn. Dz.U. z 2003 r. Nr 24, poz. 199 z późn. zm.), jako państwowa jednostka organizacyjna podległa Prezesowi Rady Ministrów (art. 14a ustawy). Rządowe Centrum Legislacji jest jednostką samodzielną pod względem organizacyjnym i finansowym, finansowaną bezpośrednio z budżetu państwa, tak samo jak ministerstwa i urzędy centralne (art. 14h).Najogólniej rzecz biorąc, RCL zostało utworzone w celu ograniczenia (przezwyciężenia) negatywnych skutków zjawiska „resortowości" w rządowym procesie tworzenia prawa. Nie zakładano natomiast pełnego przejęcia legislacji rządowej z resortów do nowo tworzonej jednostki centralnej usytuowanej przy premierze - przynajmniej w pierwszym okresie jej funkcjonowania. The Government Legislative Centre (GLC) was established on 1 January 2000 on grounds of inter alia for that purpose modified Act on Council of Ministers of 8 August 1996 (Journal of Laws No 24, item 199, as amended). It is a state organizational unit governed by the Prime Minister. Government Legislative Centre is a organizationally independent and self-financing unit, financed from the national budget directly, as well as ministries and central offices.GLC was established with the purpose to overcome negative consequences of "departmentalization" in governmental proceeding of creating law, yet not with the aim to take over the whole governmental legislation from the departments.GLC ensures the coordination oflegislation activity of the Council ofMinisters, the Prime Minister and the others governmental administration offices, and provides legal services to the Council of Ministers, in particular: works out legal and legislative positions to governmental drafts oflegal acts; coordinates the setting process of governmental drafts of legal acts, including the assessment of socio-economic effects of proposed regulations; works out in legislative respect governmental drafts of legal acts, which are referred to examine by the Council of Ministers, including their assessment in legal and editorial respect, done by the Legal Commission headed by GLC; works out governmental drafts of legal acts within the scope stipulated by the Prime Minister; edits the Journal of Law of Republic of Poland and 'Polish Monitor' Official Gazette of the Republic of Poland; operates together with the Committee of European Integration on harmonizing polish law with the requirements of the law in European Communities; operates together with the Legislative Council on providing opinions on the conformity of go verum en tal drafts of le gal acts with the Constitution of Republic of Poland and the cohesion with the legal system; controls rules laid down by governmental administration offices for implementation of le gal acts; executes other tasks stipulated in separate provisions or indicated by the Prime Minister.The coordination of legislative activity of the Govemment leads the tasks of GLC. GLC also devises fully autonomously normative acts, yet only on the official order of the Prime Minister or the Chef of the Chancellery of the Prime Minister acting on his behalf.GLC is entrusted with drafting a normative act usually when - due to legal reasons, e.g. need to resolve in the project complex and complicate problems of legal nature or, less often, due to other reasons - difficulties appeared while the draft was worked out by a competent Minister.In legislation practice GLC provides assistance to legislative services in ministries and central offices by working out, on their request, particular regulations, which formulations give rise to problems of legal nature.Ministers or heads of central offices request GLC to draft regulations or correct their preliminary version before they present it officially as a "departmental" project.A practice of direct "working" contacts is evaluated between GLC and legislators in ministries and central offices.It can be said that the procedure of creating law on govemmental level does not differ in a formal aspect from European standards, since this procedure has a formalized (official legal regulation and by-law) and institutional (existence of GLC as a unit which is formally but not politically responsible for the governmental legal process) character.